Microfluidic liquid cell chamber for scanning probe microscopy measurement application - Gillissen, Jurriaan J. J. (2019)
In this paper, we present a universal microfluidic liquid chamber device platform for atomic force microscopy (AFM), which enables to fabricate the uniform lipid bilayer on the hydrophilic surface using the solvent-assisted lipid bilayer formation method. Using this device enables us to acquire the various properties of delicate soft matter, including morphological data, and mechanical property measurements, using high-resolution AFM systems. The proposed technology is expected to provide an understanding of complicated biological materials.